Analysis of factors that affect internal whistle-blowing intentions - Rifatul Fitriyah; Rovila El Maghviroh (STIE Perbanas Surabaya, 2019)
This research aimed to find out more information and empirical evidence on the effect of managerial status, organizational commitment, locus of control, and personal cost on internal whistle-blowing intentions among the employees of Regional Government Work Unit (Satuan Kerja Perangkat Daerah/ SKPD) in Surabaya. This research used 57 employees of SKPD Surabaya as the respondents. The sample was taken using a quota sampling method. This is a quantitative research in which the data were analyzed using multiple regression analysis with SPSS 23. The results shows that the variables of managerial status, locus of control, and personal cost have no effect on internal whistle-blowing intention, while the variable of organizational commitment has an effect onit.